USING AVENA MACROSTACHYA FOR IMPROVEMENT OF OAT WINTERHARDINESS IN POLAND - B. . Lapinski; A. . Rachwalska (Труды по прикладной ботанике, генетике и селекции, 2018)
The Polish program of winter oat breeding started in 2002 from interspecific crossing of foreign winter oats with the accessions of tetraploid perennial wild species Avena macrostachya Bal. ex Coss et Dur. Single hybrids were obtained in three cross combinations. Large differences were noticed in fertility level and chromosome constitution of progeny of the intensely cloned and colchicine treated F1 hybrids. The B1F or F2 generation consisted of plants with chromosome numbers between 40 and 49, octoploids (2n=56) and plants carrying 60 to 70 chromosomes. The quasi-hexaploids of the first group were partly or completely sterile, but their chromosome complement was quickly regulated and fertility restored, usually after additional back-cross to A. sativa L. A few generations later they produced valuable breeding strains. In field experiments in Radzikow (near Warsaw) and Grodkowice (near Krakow), they showed high yielding potential and no negative effects of wild germplasm. In the dry seasons 2009 and 2013 winter oats produced yields nearly 100% higher than the spring cultivar standard. Test weight of the winter oat was also ca. 4kg/hl higher than in the spring oat. Two of the husked strains, showing winterhardiness level better than the starting A. sativa population, are in the Polish state variety trials (from 2014 and 2015) 2015. They could be recommended for the regions with stable snow cover, because they were not able to survive naked ground surface temperatures below -14oC, which happened twice in Radzikow and once in Grodkowice in the last 8 years of field trials. Especially the last winter (2015/2016) was destructive, even for the octoploids, which were earlier considered the most winter-hardy oats. The octoploids produce healthy green mass and very large plump grain, rich in protein, however they require a breeding effort to increase yield (now 50-67% of the best winter hexaploids) and to make ripening uniform. The last severe winter season revealed several new hexaploid strains, transgressive in frost resistance to the octo-ploids. The 8x or 10x sativa-macrostachya alloploids proved to be effective sources of winterhardiness for hexaploid oat.